Eosinophilic esophagitis: Epithelial mesenchymal transition contributes to esophageal remodeling and reverses with treatment - Kagalwalla, Amir F.; Akhtar, Noorain; Woodruff, Samantha A.; Rea, Bryan A.; Masterson, Joanne C.; Mukkada, Vincent; Parashette, Kalyan R.; Du, Jian; Fillon, Sophie; Protheroe, Cheryl A.; Lee, James J.; Amsden, Katie; et al. (Journal of allergy and clinical immunology, 2012)
Mechanisms underlying esophageal remodeling with subepithelial fibrosis in subjects with eosinophilic esophagitis (EoE) have not been delineated. We sought to explore a role for epithelial mesenchymal transition (EMT) in subjects with EoE and determine whether EMT resolves with treatment. Esophageal biopsy specimens from 60 children were immunostained for epithelial (cytokeratin) and mesenchymal (vimentin) EMT biomarkers, and EMT was quantified. Subjects studied had EoE (n = 17), indeterminate EoE (n = 15), gastroesophageal reflux disease (n = 7), or normal esophagus (n = 21). EMT was analyzed for relationships to diagnosis, eosinophil counts, and indices of subepithelial fibrosis, eosinophil peroxidase, and TGF-β immunostaining. EMT was assessed in pretreatment and posttreatment biopsy specimens from 18 subjects with EoE treated with an elemental diet, 6-food elimination diet, or topical corticosteroids (n = 6 per group). TGF-β1 treatment of esophageal epithelial cells in vitro for 24 hours induced upregulation of mesenchymal genes characteristic of EMT, including N-cadherin (3.3-fold), vimentin (2.1-fold), and fibronectin (7.5-fold). EMT in esophageal biopsy specimens was associated with EoE (or indeterminate EoE) but not gastroesophageal reflux disease or normal esophagus and was correlated to eosinophil counts (r = 0.691), eosinophil peroxidase (r = 0.738), and TGF-β (r = 0.520) immunostaining and fibrosis (r = 0.644) indices. EMT resolved with EoE treatments that induced clinicopathologic remission with reduced eosinophil counts. EMT decreased significantly after treatment by 74.1% overall in the 18 treated subjects with EoE; pretreatment versus posttreatment EMT scores were 3.17 ± 0.82 versus 0.82 ± 0.39 (P < .001), with similar decreases within treatment groups. Pretreatment/posttreatment EMT was strongly correlated with eosinophil counts for combined (r = 0.804, P < .001) and individual treatment groups. EMT likely contributes to subepithelial fibrosis in subjects with EoE and resolves with treatments that decrease esophageal inflammation, and its resolution correlates with decreased numbers of esophageal eosinophils.